1971
DOI: 10.1002/pssa.2210060128
|View full text |Cite
|
Sign up to set email alerts
|

Shell Model Calculation of Thermal Expansion of Alkali Halides and Magnesium Oxide

Abstract: The microscopic Grüneisen parameters and the temperature dependence of the thermal Grüneisen parameter have been calculated in the quasi‐harmonic approximation from an anharmonic shell model for MgO, LiF, NaF, NaI, KCl, KBr, KI, RbCl, RbBr, and RbI. The shell model contains six harmonic and five anharmonic parameters which are determined from experimental elastic, dielectric, and optical data. Anharmonic effects are partly eliminated by referring all quantities to constant volume corresponding to 0 °K. The cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Tn the case of positive moments the experimental data suggest a different behavior y ( 0 ) < y ( 2 ) < y(4). The present theoretical results show a behaviour y(2) > y ( 4 ) > y ( 6 ) which is similar to those obtained in alkali halides [15]. Since the experimentally deduced values of higher order moments are less reliable, it is difficult to conclude anything a t this stage.…”
Section: Moments Y ( N )supporting
confidence: 82%
“…Tn the case of positive moments the experimental data suggest a different behavior y ( 0 ) < y ( 2 ) < y(4). The present theoretical results show a behaviour y(2) > y ( 4 ) > y ( 6 ) which is similar to those obtained in alkali halides [15]. Since the experimentally deduced values of higher order moments are less reliable, it is difficult to conclude anything a t this stage.…”
Section: Moments Y ( N )supporting
confidence: 82%
“…Chang & Barsch (1973) concluded that for single-crystal spinel, the first assumption is bad. Based on Achar & Barsch (1971) and Barsch & Achar (1972), Chang & Barsch concluded that the second assumption in Anderson's derivation is valid for T E 6/2. In short, (39) holds in the form 6 ( g~) oc C, for T 2 -P 2 independent of assumptions regarding Gruneisen parameters.…”
Section: Results and Comparison With Other Experimentsmentioning
confidence: 99%